Contributions of 5-HT Neurons to Respiratory Control: Neuromodulatory and Trophic Effects - Hodges, Matthew R. (2008)
Serotonin (5-hydroxytryptamine; 5-HT) is a neurotransmitter produced by a small number of neurons in the midbrain, pons and medulla. These neurons project widely throughout the neuraxis, where they release 5-HT and co-localized neuropeptides such as substance P (SP) and thyrotropin-releasing hormone (TRH). Each of these chemicals produce effects largely through G protein-coupled receptors, second messenger systems and subsequent neuromodulatory effects on target neurons. Emerging evidence suggests that 5-HT has additional modes of action during development and in adult mammals, including trophic effects (neurogenesis, cell differentiation, proliferation, migration and maturation) and influences on synaptic plasticity. Here, we discuss some of the neuromodulatory and trophic roles of 5-HT in general and in the context of respiratory control, as well as the regulation of release of modulatory neurotransmitters from 5-HT neurons. Future directions of study are also discussed.